PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL PADA PEMERINTAH KABUPATEN NIAS BARAT PERIODE 2016 - 2021 - PURBA, IMELDA RIMENDA; GULO, VIVIN TRI INDAWATI (UNIKA Santo Thomas, 2022)
This study aims to obtain empirical evidence of the effect of Regional Original Income (PAD), and General Allocation Funds (DAU), on Capital Expenditures in West Nias Regency for the 2016-2021 period. This type of research is quantitative research. The data used in this study are secondary data. The population in this study includes reports on budget realization from establishment until 2021. The sample is budget realization reports from 2016-2021, which is for 6 years. The sampling technique in this study was using purposive sampling. The data analysis used to test the hypothesis was multiple linear regression with a significance level of 55 and using SPSS version 23. partially and simultaneously has no effect on regional spending.